Exploring the bioactive compounds of Carica papaya leaves: phytol’s role in combatting antibiotic-resistant bacteria - Alhodieb, Fahad Saad; Farid, Maira; Sabir, Maimoona; Nisa, Sobia; Sarwar, Sumaira; Abbas, Sidra (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionAntibiotic resistance is a pressing global challenge, complicating the treatment of infectious diseases caused by multidrug-resistant microorganism. For centuries, medicinal plants have been a cornerstone of natural remedies, offering bioactive compounds with therapeutic potential.MethodsThe study investigate the phytochemical screening and antibacterial efficay of Carica papaya leaf extract, focusing on its impact against three Gram-negative bacterial pathogens i.e., Escherichia coli, Helicobacter pylori, and Salmonella enterica serovar Typhi, are major contributors to gastrointestinal infections worldwide, often leading to severe inflammation and chronic health complications. ResultsThe phytochemical screening revealed the presence of phenols and flavonoids, which are key contributors to the extract’s biological activity. GC-MC analysis identified 27 bioactive compounds, with phytol emerging as a prominent constituent, detected at a peak retention time of 18.712 minutes. Antibacterial assays demonstrated significant efficacy, with inhibitory zones ranging from 10 to 20 mm against the tested pathogens. Molecular docking further highlighted phytol’s strong binding affinities to crucial bacterial proteins, including DNA gyrase (E. coli), Vacuolating cytotoxin A (H. pylori) from, and Dihydrofolate reductase (Salmonella enterica serovar Typhi). Notably, phytol exhibited the highest binding energy (-6.64 kcal/mol) with DHFR, indicating a robust interaction that underscores its potential as a targeted antibacterial agent against Salmonella enterica serovar Typhi.DiscussionThese findings position phytol as a promising lead compound for developing novel antibacterial therapies. Its strong activity against multidrug-resistant pathogens suggests potential for further exploration, though additional research is needed to assess its role in resistance modulation or prevention.